Documenting the challenges of conducting research on sexual and reproductive health and rights (SRHR) of persons with disabilities in a lowand-middle income country setting: Lessons from Bangladesh - Amin, Amina; Das, Adity Shayontony; Kaiser, Adrita; Azmi, Raia; Rashid, Sabina Faiz; Hasan, Md Tanvir (BMJ Journals, 2022)
This article was published in BMJ Global Health by BMJ Journals [© Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjgh-2020-002904 The Journal's website is at: https://gh.bmj.com/content/5/12/e002904